An architectural style of product lines for distributed processing systems, and practical selection method. - Morisawa, Yoshitomi
When implementing an application system in a distributed computing environment, several architectural questions arise, such as how and where computing resources are arranged, and how the communication among computing resources are implemented. To simplify the process of making these choices, we have developed an architectural style for distributed processing system. The style classifies product lines for distributed processing systems into nine categories based on the location of data storage and the style of processing between client and server. This paper describes our architectural style and proposes a simple but practical method to select an appropriate architectural style for developing an application system. We apply this selection method in concrete real application systems.
Keywords: Software; Software engineering; Software architectures; Domain-specific architectures; Computer systems organization; Computer communication networks; Distributed systems; Distributed applications; Design; Architectural style; Distributed computing model; Distributed processing system; Product lines; Software architecture